THE RIGHT TO DATA PROTECTION VERSUS “SECURITY”: CONTRADICTIONS OF THE RIGHTS-DISCOURSE IN THE BRAZILIAN GENERAL PERSONAL DATA PROTECTION ACT (LGPD) - Viana da Silva, Marcos Vinicius; da Luz Scherf, Erick; da Silva, Jose Everton (Revista Direitos Culturais, 2020)
The protection of personal data in the cyberspace has been an issue of concern for quite some time. However, with the revolutions in information technology, big data and the internet of things, data privacy protection has become paramount in an era of free information flows. Considering this context, this research intends to shine a light on the experience of Brazil regarding data privacy protection, through the analysis of a brand new bill passed by Congress: the Brazilian General Personal Data Protection Act. Our assessment of the legislation was made from the perspective of a human rights-based approach to data, aiming to analyze both advancements, limitations and contradictions of the rights-discourse in the LGPD. Our main conclusions were that the (public and national) security rhetoric, also present in the bill, can create a state of exception regarding the processing of personal data of those considered “enemies of the state”, which may result in violations of fundamental rights and procedural guarantees.